Aspects of Developing A Methodology for Managing Digital Financial Assets - A. Yu. Proskuryakov (Статистика и экономика, 2023)
The purpose of the study is to highlight the key aspects necessary for the formation of a methodology for designing systems for managing trading operations over cryptocurrencies. The methodology of designing digital asset management systems defines a set of rules for using methods, models and algorithms required to build systems that solve the complex problem of managing trading operations over digital economy assets. For this purpose, the dynamics and trends of pricing of digital investment and financial assets are investigated to identify the peculiarities and specific patterns of cryptocurrency, taking into account the mathematical model of issuance in the conditions of a dynamic crypto-asset market, functioning continuously and forming cyclicality and wave structures.Materials and methods. The object of the study is the dynamics of value indicators of the market of digital financial assets and digital currencies. The subject of the study is methods, models and algorithms for automated monitoring and management of digital financial assets and cryptocurrencies. The methodological basis of the research is formed by blockchain technologies, modeling and mathematical statistics methods, artificial intelligence methods. The statistical information base of the research is formed on the basis of the history of Tradingview’s value quotations from international trading exchanges of digital currencies, as well as by Coinmarketcap and Coingecko cryptoasset market integrators. Problems of modeling processes in economic systems are considered, the problem of optimal control is defined. A critical analysis of the state in the tasks of economic modeling is carried out, taking into account the uncertainty caused by social and psychological reasons.Results. The proposed methodology offers a comprehensive solution to the problem of managing digital financial assets and other financial instruments based on blockchain technology. Digital currencies act as the management object of the proposed methodology, the initial information is a vector of parameters that determine the sensitivity of the system to the perturbing influences of the external environment and the requirements for the expected management results. In accordance with the scientific novelty of the research and methodology, a set of interrelated research stages is formed, consisting of an ordered cascade of methods, models and algorithms that perform preliminary analysis, processing and forecasting of financial time series of value indicators.Conclusion. New blockchain technologies and the emergence of Chat GPT (generative pre-trained transformer) pose new challenges to society, which hopes to utilize such solutions, including for economic tasks. With the help of prediction-free methods and artificial neural networks it is possible to design software systems, thanks to which it is possible to increase the efficiency of trading operations at optimal risks in automatic and automated mode of trade execution. The proposed methodology of management with auxiliary intellectual analysis of time series and application of combined method of decision-making allows managing the portfolio of a new asset class of digital currencies based on blockchain technologies. Taking into account the technical similarity of digital currencies with digital financial assets, it is possible to use the methodology also for the creation of digital financial asset management systems.